Persistent postural perceptual vertigo and vestibular migraine. Case report - Ekaterina N. Zastenskaya; Ludmila M. Antonenko (ZAO "Consilium Medicum", 2023)
Persistent postural perceptual vertigo (PPPV) and vestibular migraine (VM) are common causes of vertigo. However, despite the typical clinical presentation of PPPV and VM, these diagnoses are rarely made, and dizziness is considered a consequence of other diseases, such as cerebrovascular disorders (chronic cerebral ischemia, vertebrobasilar insufficiency), cervical spine instability, or the manifestation of vegetative dystonia syndrome. This article describes a clinical case of a patient with PPPV and VM. The diagnosis is based on the clinical presentation matched with the diagnostic criteria and an in-depth examination using additional methods to rule out other causes of dizziness. Current evidence on clinical and instrumental diagnostics of the disorders is presented.